2019
DOI: 10.1021/jacs.9b02985
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Post-assembly Modification Triggers Structural Transformations of Borromean Rings

Abstract: Experimental procedures, spectroscopic data, and X-ray crystallography (PDF) X-ray data for 1 (CCDC 1901497) (CIF) X-ray data for 2 (CCDC 1901498) (CIF) X-ray data for 3-BR (CCDC 1901499) (CIF) X-ray data for 5 (CCDC 1901500) (CIF) X-ray data for 6 (CCDC 1901501) (CIF) X-ray data for 7 (CCDC 1901502) (CIF)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 26 publications
0
40
0
Order By: Relevance
“…In order to use the ligand exchange for the post-synthetic modification of responsive host molecules, we have to employaparent host framework that is stableu nder the conditions used for the modification, whereas self-assembledc ages sometimes undergo ligand exchange in the skeletal coordination bonds which leads to an undesired disruption of the host structure and/or size conversion such as cage-to-cage transformations. [9] Therefore, the host structures for post-synthetic modification based on ligand exchange should contain two kinds of coordination bonds;o ne is sufficiently inert to firmly hold the metali onsi nthe structure and the other is sufficiently labile to enablet he ligand exchange for the post-syntheticm odification. [10] Chelatec oordination sites incorporated in af ully organic framework may also be usefult oh old metal ions, on whichagreaterv ariety of modifiers can be introducedb yc oordination bonds.…”
Section: Introductionmentioning
confidence: 99%
“…In order to use the ligand exchange for the post-synthetic modification of responsive host molecules, we have to employaparent host framework that is stableu nder the conditions used for the modification, whereas self-assembledc ages sometimes undergo ligand exchange in the skeletal coordination bonds which leads to an undesired disruption of the host structure and/or size conversion such as cage-to-cage transformations. [9] Therefore, the host structures for post-synthetic modification based on ligand exchange should contain two kinds of coordination bonds;o ne is sufficiently inert to firmly hold the metali onsi nthe structure and the other is sufficiently labile to enablet he ligand exchange for the post-syntheticm odification. [10] Chelatec oordination sites incorporated in af ully organic framework may also be usefult oh old metal ions, on whichagreaterv ariety of modifiers can be introducedb yc oordination bonds.…”
Section: Introductionmentioning
confidence: 99%
“…In order to study the kinetics of the conversion of Solomon link 1 into metallarectangle 2 , a 60 m m (with respect to Cp*Rh) solution of 1 in CD 3 OD was diluted to around 1.0 m m and monitored by quantitative 1 H NMR experiments (Figure S21). Linear regression analysis of the experimental data (Figure S22) showed that the conversion process could be well fitted by the rate law of a first‐order reaction, giving a conversion reaction rate coefficient of k =0.0493 min −1 at 298 K with an adjusted R 2 value of 0.9911, as shown in Table S1.…”
Section: Resultsmentioning
confidence: 90%
“…The resultsi ndicatedt hat the self-assembly favors the formation of Solomonl ink 1 at higher concentrations, whereas at lower concentrations the equilibrium shifts in favor of trapezoidal metallacycle 2.I no rder to study the kineticso ft he conversion of Solomonl ink 1 into metallarectangle 2,a6 0mm (with respectt oC p*Rh) solutiono f1 in CD 3 OD was diluted to around1 .0 mm and monitored by quantitative 1 HNMR experiments ( Figure S21). Linear regression analysiso ft he experimental data ( Figure S22) showedt hat the conversion process could be well fitted by the rate law of af irst-order reaction, [15] giving ac onversion reaction rate coefficient of k = 0.0493 min À1 at 298 Kw ith an adjusted R 2 value of 0.9911, as shown in Ta ble S1.…”
Section: Dynamicinterconversion Between Solomon Link and Trapezoidal mentioning
confidence: 85%
“…Assembled supramolecular architectures offer a controllable platform at the molecular level to mimic the function of biosystems [3] . Adaptive transformations have also been widely seen in such artificial hosts with stimuli‐responsiveness to anion, [4] solvent, [5] concentration, [5a, 6] stoichiometric ratio of components, [5f, 7] post‐modification [6b, 8] chemical fuel, [9] and so on [5f, 10] . Guided by the induced‐fit mechanism, guest‐templated synthesis offers an important route toward otherwise inaccessible complicated host–guest complexes [5f, 11] .…”
Section: Methodsmentioning
confidence: 99%